2011
DOI: 10.18860/iq.v0i0.271
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pengembangan BMT (Baitul Maal Wa Tamwil) Dalam Memberdayakan Usaha Kecil Menengah

Abstract: The sustainability of syariah microfinance institution depends on the organization it professionally, and the strategic implementation comprehensively in positioning BMT (Baitul Maal wa Tamwil) as one of microfinance intermediary institution. The BMT’s existence created positive public image to participate in  developing BMT and improving people wealth broadly. Optimism toward BMT’s prospect is a main capital in developing BMT concept not only  as a development agent, but also as a profit institution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Human resource productivity, according to Ely Siswanto, is managerial improvement and financial management that will affect BMT efficiency in credit financing for small and medium sectors [15], further related to financial performance, Camilla Janner Lislevand (2012) found that most MFIs were much leveraged. Because of total short-term debt to assets and debt to assets has a positive and significant effect on the cost of funds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human resource productivity, according to Ely Siswanto, is managerial improvement and financial management that will affect BMT efficiency in credit financing for small and medium sectors [15], further related to financial performance, Camilla Janner Lislevand (2012) found that most MFIs were much leveraged. Because of total short-term debt to assets and debt to assets has a positive and significant effect on the cost of funds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Siswanto (Siswanto 2009) dalam penelitiannya yang berjudul "Strategi Pengembangan Baitul Maal Wattamwil (BMT) dalam Memberdayakan Usaha Kecil dan Menengah" berupaya untuk mengidentifikasi dan menganalisis model BMT yang dapat memberdayakan usaha kecil, serta dapat menemukan strategi dan upaya agar BMT mampu memberdayakan Usaha Kecil Menengah. Penelitian ini dilakukan menggunakan metode deskriptif dengan teknik analisis analisa isi tema dari data literatur dan penelitian sebelumnya terkait penelitiannya.…”
Section: Pendahuluanunclassified
“…Etymologically, bait maal wa attamwil can be interpreted as a place or media for financial management (Siswanto 2008).…”
Section: Introductionmentioning
confidence: 99%